2010
DOI: 10.1111/j.1471-0528.2010.02519.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of human papillomavirus testing in the management of women with low‐grade abnormalities: multicentre randomised controlled trial

Abstract: Objective To assess the value of a single human papillomavirus (HPV) test in making decisions on management of women with cervical cytology showing borderline nuclear abnormality (BNA) or mild dyskaryosis. In particular, to determine whether information on high-risk (hr) HPV status would be valuable in the choice between (1) cytological surveillance versus immediate referral to colposcopy, and (2) at colposcopy, between biopsy and recall versus immediate large loop excision of the transformation zone (LLETZ).D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…4 At randomisation, an endocervical sample was taken to identify the presence of DNA of 14 high-risk human papillomavirus types (hrHPV) using a polymerase chain reaction (PCR) with GP5+/6+ primers and enzyme immunoassay identification. The results of HPV testing did not interfere with management.…”
Section: Tombola Trialmentioning
confidence: 99%
“…4 At randomisation, an endocervical sample was taken to identify the presence of DNA of 14 high-risk human papillomavirus types (hrHPV) using a polymerase chain reaction (PCR) with GP5+/6+ primers and enzyme immunoassay identification. The results of HPV testing did not interfere with management.…”
Section: Tombola Trialmentioning
confidence: 99%
“…Giving the fact that HPV testing has been shown to have similar sensitivity but more overdiagnosis than the Pap test [25][26][27][28], and also giving the fact that false negative results may be higher than previously suspected [25,26,32], primary screening with HPV testing in European countries as well as in the U.S. should be reconsidered. Resources saved in molecular testing may well be addressed in implementing vaccination strategies that are still underused and possibly must include males as well as women [44,45].…”
Section: Resultsmentioning
confidence: 99%
“…This false negative rate is similar to that observed by Cotton and coll. who showed that 22% of women who had CIN 2 or worse were HPV negative at baseline (TOMBOLA trial) [26]. It is difficult to accept these figures when one talks of extending rescreening intervals such as those proposed by HPV testing algorithms.…”
Section: Background Studiesmentioning
confidence: 99%
“…At the same conclusions arrived Cotton and coll. showing a false negative rate of 22% in women with a high grade lesions or worse who tested HPV negative at baseline (TOMBOLA trial) [14]. Nevertheless, a study designed to evaluate the efficacy of HPV-based strategies in four European randomised controlled trials showed that HPV testing was supposed to provide 60-70% greater protection against cervical cancer compared with cytology [15].…”
mentioning
confidence: 99%